2014
DOI: 10.1037/a0036889
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness in a day: Activity engagement, time alone, and experienced emotions.

Abstract: The experience of chronic loneliness has been associated with poorer physical health and well-being, including declines in cardiovascular health and higher levels of distressed affect. Given the long-term effects of loneliness on health and well-being, much research has focused on loneliness in older age. The purpose of the current study was to obtain a more detailed picture of the experience of loneliness in midlife and older adulthood by incorporating the context of a day’s activities. We use a modified day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 38 publications
(55 reference statements)
6
55
0
Order By: Relevance
“…Worthwhile ratings were inversely associated not only with loneliness and living alone, but also with time spent alone on the previous day; a similar pattern has been described in the Health and Retirement Study (21). The observation that people with higher worthwhile ratings spent more time walking or exercising is consistent with the physical activity results.…”
Section: Discussionsupporting
confidence: 78%
“…Worthwhile ratings were inversely associated not only with loneliness and living alone, but also with time spent alone on the previous day; a similar pattern has been described in the Health and Retirement Study (21). The observation that people with higher worthwhile ratings spent more time walking or exercising is consistent with the physical activity results.…”
Section: Discussionsupporting
confidence: 78%
“…Previous research has suggested that loneliness is less a matter of spending time alone and more a matter of not experiencing a gain in positive emotions from social activity (Hawkley, Burleson, Berntson, & Cacioppo, 2003; Queen, Stawski, Ryan, & Smith, 2014). Also, prior research indicates that whereas lonely individuals find their interactions with close others to be less rewarding than non-lonely individuals do, fewer differences exist in interactions with acquaintances and strangers (e.g., Tsai & Reis, 2009; Williams & Solano, 1983).…”
Section: Brief Discussion and Introduction To Studymentioning
confidence: 99%
“…It is also an important indicator of earlier functional decline and other negatives outcomes. Additionally, numerous data have shown the effects of decreased social participation on social isolation 5,11 and loneliness in old age 12 . The effects of social participation on the elderly's health and well-being have been proven in several knowledge fields, with robust available data analyzing this phenomenon as independent variable, factor or predictor.…”
Section: ▄ Introductionmentioning
confidence: 99%